AUTONOMOUS VEHICLES – TODAY’S LEGAL CHALLENGES FOR TOMORROW - Mitkevičius, Vilius (Teisė, 2017)
This paper analyses the concept of autonomous vehicles and the legality of using them in Lithuania today, as well as the main legal questions related to the use of an autonomous vehicle, and how they should be answered in order to ensure a fluent adoption of this innovation into societal relations.